Penerapan Rancangan Eksperimen Satu Faktor untuk Mengetahui Pengaruh Jenis Bahan Bakar terhadap Jarak Tempuh Sepeda Motor - Dino Caesaron (Universitas Bunda Mulia, 2017)
The increasing number of vehicles is followed by the increasing amount of fuel consumption. In fact, the availability of petroleum fuel is getting decreased, while we know that fuel derived from petroleum is nonrenewable. Therefore, we conducted an experiment about the effect of four types of fuel to the distance traveled by the motorcycle media (Mega Pro). The experiments were done by using a factorial design with a single factor (ANOVA), on a different day in the implementation of the experiment as a nuisance factor. From the results of this research, we know that the fuel type affects to vehicle mileage. The fuel that has the longest mileage is Pertamax Plus. A significant degree of the fuel affects to a distance is 0.000.Keywords: ANOVA, Factorial Design, Nuisance Factor.